2016
DOI: 10.1080/13506285.2017.1314399
|View full text |Cite
|
Sign up to set email alerts
|

Carryover of scanning behaviour affects upright face recognition differently to inverted face recognition

Abstract: Face perception is characterised by a distinct scanpath (Althoff & Cohen, 1999). While eye movements are considered functional, there has not been direct evidence that disrupting this scanpath affects face recognition performance. The present experiment investigated the influence of an irrelevant lettersearch task (with letter strings arranged horizontally, vertically or randomly) on the subsequent scanning strategies in processing upright and inverted famous faces. Participants' response time to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…For instance, when participants were asked to detect hazards in driving stimuli, not only did the orientation of the preceding letter search influence eye movements to the driving stimuli, but response times were slower following a vertical letter search compared to following a horizontal letter search (Hills, Thompson, & Pake, 2018;Thompson & Crundall, 2011). A vertical letter search has additionally been found to negatively impact the ability to recognise upright faces (Hills, Mileva, Thompson, & Pake, 2017). It may be argued that this impairment to performance reflects an effect of fatigue rather than attentional shifting, on the basis that a vertical search is more difficult, takes longer, and thus leads to performance costs in a subsequent task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when participants were asked to detect hazards in driving stimuli, not only did the orientation of the preceding letter search influence eye movements to the driving stimuli, but response times were slower following a vertical letter search compared to following a horizontal letter search (Hills, Thompson, & Pake, 2018;Thompson & Crundall, 2011). A vertical letter search has additionally been found to negatively impact the ability to recognise upright faces (Hills, Mileva, Thompson, & Pake, 2017). It may be argued that this impairment to performance reflects an effect of fatigue rather than attentional shifting, on the basis that a vertical search is more difficult, takes longer, and thus leads to performance costs in a subsequent task.…”
Section: Introductionmentioning
confidence: 99%
“…It may be argued that this impairment to performance reflects an effect of fatigue rather than attentional shifting, on the basis that a vertical search is more difficult, takes longer, and thus leads to performance costs in a subsequent task. However, if that was the case it would also be expected that carry-over would be greater with increased repetition of the letter search task, yet studies have consistently shown that the persistence of attentional set to the second task does not vary according to whether participants complete one or three letter searches (Hills et al, 2017;Hills et al, 2018;Thompson & Crundall, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence to show that the topdown attentional set adopted to complete one task can persist to a second task, influencing attention, visual search, and performance. This has been demonstrated in low-level tasks measuring the bias of attention towards previously relevant information (e.g., Leber & Egeth, 2006;Thompson et al, 2007) and to previously relevant areas of space (e.g., Hills et al, 2017;Longman et al, 2013;Thompson & Crundall, 2011;Thompson et al, 2021;Wendt et al, 2017). Longman et al (2013Longman et al ( , 2017 argue that the carryover of attentional set (which they refer to as attentional inertia) occurs because a set switch requires adoption of the new attentional settings and inhibition of the old settings.…”
Section: Discussionmentioning
confidence: 99%
“…Since the investigation of Thompson and Crundall (2011) , several other studies have demonstrated the carry-over of top-down attentional settings, using the same or similar paradigm (e.g., Hills et al, 2016 , 2017 ; Thompson et al, 2015 ). However, it may again be argued that while this paradigm is more “dynamic,” it is still limited because the tasks are always presented to the same spatial location.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the right-side bias for inverted faces was not specific to other-race facial features. This may reflect the fact that inverted faces cannot be processed holistically (Crookes et al, 2013 ; Hills et al, 2016 ) but require feature-based processing. To process inverted faces, when holistic strategies cannot be applied, participants may resort to analytic strategies by focusing on certain features in the original face (e.g., eyebrow slant and lip curvature) and matching them with the chimeras.…”
Section: Discussionmentioning
confidence: 99%